2009
DOI: 10.1177/1077559509337893
|View full text |Cite
|
Sign up to set email alerts
|

Fathers and Maternal Risk for Physical Child Abuse

Abstract: This study set out to examine father-related factors predicting maternal physical child abuse risk in a national birth cohort of 1,480 families. In-home and phone interviews were conducted with mothers when index children were 3 years old. Predictor variables included the mother–father relationship status; father demographic, economic, and psychosocial variables; and key background factors. Outcome variables included both observed and self-reported proxies of maternal physical child abuse risk. At the bivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 52 publications
3
58
1
3
Order By: Relevance
“…Waldfogel et al's own analyses of data from FFCWS children at Age 5 confirmed that family structure made little difference to cognitive outcomes; what seemed to matter most were changes in family structure over time. Also using FFCWS data, Guterman, Lee, Lee, Waldfogel, and Rathouz (2009) found few differences between cohabiting, single, and married mothers of 3-year-olds in rates of aggressive or punitive parenting after controlling for sociodemographic and psychosocial variables.…”
Section: Child Well-being and Parental Cohabitationmentioning
confidence: 99%
“…Waldfogel et al's own analyses of data from FFCWS children at Age 5 confirmed that family structure made little difference to cognitive outcomes; what seemed to matter most were changes in family structure over time. Also using FFCWS data, Guterman, Lee, Lee, Waldfogel, and Rathouz (2009) found few differences between cohabiting, single, and married mothers of 3-year-olds in rates of aggressive or punitive parenting after controlling for sociodemographic and psychosocial variables.…”
Section: Child Well-being and Parental Cohabitationmentioning
confidence: 99%
“…The value of promoting healthy father involvement rests on the observation that father-related variables (e.g., employment status, age, educational attainment, relationship with the mother and the child, and potential use of psychoactive substances) impact the risk for child neglect and abuse (Guterman & Lee, 2005; Guterman et al, 2009). There are also CPS policy-driven expectations for involving fathers that demand attention to all the factors at play (Sylvester & Reich, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Involvement by a supportive father reduces the likelihood that mothers will use harsh punitive parenting with a child (Crockenberg, 1987; Guterman et al, 2009) or develop mental health issues (Black et al, 2002) that place children at risk for maltreatment. Even when fathers do not reside with their children, fathers can positively impact their children’s intellectual (Downer, Campos, McWayne, & Gartner, 2008) and social development (Flouri, 2006; Flouri & Buchanan, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Guterman, Lee, Lee, Waldfogel, and Rathouz (2009) demonstrated this by showing how a healthy father-child relationship was associated with a reduced risk of the mother physically abusing her child. This finding adds to a substantial body of research that has amply documented the benefits to children of strong, healthy relationships with fathers or father figures (Lamb, in press).…”
mentioning
confidence: 84%